Community Action Reports - Myron Allukian, Jr., DDS, MPH (Blackwell Synergy, 2001)
I am pleased to introduce Community Action Reports, and to be the associate editor for this new section in the JPHD. This exciting new section provides an opportunity for public health professionals to share firsthand with their colleagues around the world meaningful and significant experiences in the field. It will provide the dental public health community an opportunity to share significant achievements, initiatives, and programs that would normally not be published in a refereed journal or would take so long to be published that their significance is diminished.